1 / 6

Mastering the Remainder Theorem in Polynomial Equations

Learn how to find factors, roots, and remainders in polynomials using the Remainder Theorem. Understand f(x) notation and factorizing techniques. Practice exercises provided.

gentilem
Download Presentation

Mastering the Remainder Theorem in Polynomial Equations

An Image/Link below is provided (as is) to download presentation Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author. Content is provided to you AS IS for your information and personal use only. Download presentation by click this link. While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server. During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

Presentation Transcript


  1. Lesson 4-Remainder Theorem Objectives : - The remainder and Factor theorems - It’s used to help factorise Polynomials - It’s used to help find roots of equation - It’s used to help find remainder without actually dividing ML4 MH

  2. f(x) Notation • f(x) stands for “factor of x” • f(x) notation is often used instead of “y” • So we can say f(0) = 03-7(0)2+5(0)-6 = -6 f(1) = 13-7(1)2+5(1)-6 = -7 f(2) = 23-7(2)2+5(2)-6 = -16 f(-1)= (-1)3-7(-1)2+5(-1)-6 = -19 ML4 MH

  3. Consider this division x-2 is a factor of x3-3x2-10x+24 Calculate f(2) f(2)=0 • __x2-x-12____ • (x-2) | x3-3x2-10x+24 • x3-2x2 • -x2-10x • -x2+ 2x • - 12x+24 • - 12x+24 • 0 If f(a)=0, then (x-a) is a factor of the Polynomial so if f(a) = 0 the remainder is zero ML4 MH

  4. Consider this division Calculate f(-2) What do you notice f(-2)= 2(-2)3+3(-2)2-(-2)+1 f(-2)=-1 If a polynomial f(x) is divided by (x – a), the remainder is the constant f(a), and f(x) = q(x) ∙ (x – a) + f(a) where q(x) is a polynomial with degree one less than the degree of f(x). Why is this ?? ML4 MH

  5. This is because A division is essentially : When x=a i.e. f(a) if f(a)=0 -> factor (x-a) otherwise f(a)=R -> (x-a) gives R Divisor d(x) is of the form (x-a) Do exercise 3c page 94 ML4 MH

  6. Summary • If a polynomial f(x) is divided by (x – a), • the remainder is the constant f(a), and • f(x) = q(x) ∙ (x – a) + f(a) • where q(x) is a polynomial with degree • one less than the degree of f(x). ML4 MH

More Related